Changing Perceptions of Corruption in the Netherlands: From Early Modern Pluralism to Modern Coherence. Issue 1 (February 2013) - Kerkhoff, Toon
Corruption in the Netherlands: Changing Perceptions from Early Modern Pluralism to Modern Coherence: This article juxtaposes Early Modern Dutch debates on and perceptions of political corruption with long-nineteenth-century ones. The article shows a transition from early modern value pluralism to late eighteenth and early nineteenth century coherent political views on corruption, despite some remaining «pockets» of Normenpluralität. Partly due to a very different socio-political environment, late-eighteenth and early-nineteenth-century Dutch administrators drew a clearer line between the public and the private spheres than had previously been the case. Also, the article demonstrates that the democratisation and politicisation that took place at the time exerted considerable influence on changes in vocabulary and perceptions of political corruption. It shows how at the start of the long nineteenth century the line between corrupt and non-corrupt behaviour came to be based on «new», or at least re-emphasized, public values such as representation, accountability, and a broader notion of the public – now national – interest.